1969
DOI: 10.2172/4152672
|View full text |Cite
|
Sign up to set email alerts
|

EXAMINATION OF STAINLESS-STEEL-CLAD ThO$sub 2$--UO$sub 2$ FUEL RODS AND ZIRCALOY-2 CAN AFTER OPERATION FOR 442 EFPD IN THE INDIAN POINT REACTOR. Final Report, Volume 1 of 3 Volumes.

Abstract: As used in the above, "person acting on behalf of the Commission" includes any employee or contractor of the Commission, or employee of such contractor, to the extent that such employee or contractor of the Commission, or employee of such contractor prepares, dissenninates, or provides access to, any mfornnation pursuant to his employment or contract with the Commission, or his employnnent with such contractor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…91 cm 304 ss 0.76 cm 0.05 cm 4 at.% Inlet 250 0 ; outlet 300 0 C 10 MPa than 2%, regardless of fuel enrichment or burnup. Baroch et al (1969) pointed out that approximately the same amount' would be released from U0 2 operated under similar conditions. 5.5 to 9.5 cm 3 185 to 315 kPa 18 to 52% 5 to 25% 5.1 to 7.2 0.66 to 2.03 at.% 1.0 to 2.4% experiments were carried out at the Bettis Atomic Power Laboratory in Pittsburgh, Pennsylvania.…”
Section: Thorium Utilization Programmentioning
confidence: 96%
See 2 more Smart Citations
“…91 cm 304 ss 0.76 cm 0.05 cm 4 at.% Inlet 250 0 ; outlet 300 0 C 10 MPa than 2%, regardless of fuel enrichment or burnup. Baroch et al (1969) pointed out that approximately the same amount' would be released from U0 2 operated under similar conditions. 5.5 to 9.5 cm 3 185 to 315 kPa 18 to 52% 5 to 25% 5.1 to 7.2 0.66 to 2.03 at.% 1.0 to 2.4% experiments were carried out at the Bettis Atomic Power Laboratory in Pittsburgh, Pennsylvania.…”
Section: Thorium Utilization Programmentioning
confidence: 96%
“…Core 1 (the initial core) of the Indian Point Reactor operated satisfactorily for over 3 years (442 effective full-power days) and attained a burnup of 4 at.% (Deddens and Freyberg 1965;Prestile and Edlund 1966;Baroch and Bishop 1968). After the discharge of Core 1, 13 fuel rods were selected for detailed examination (Baroch et al 1969). The lack of pellet distortion and cladding strains indicated that irradiation-induced fuel swelling was minimal.…”
Section: Thorium Utilization Programmentioning
confidence: 99%
See 1 more Smart Citation